DIAGNOSIS, BIOLOGICAL AND/OR SOCIAL DEATH AS A HORIZON IN PEOPLE LIVING WITH HIV/AIDS - Cardoso, Talita Miranda Pitanga Barbosa; Silva, Ana Beatriz Ferreira Barros da; Marinho, Marcia Cristina Graça; Souza, Marcio Costa de (Revista de Psicologia, 2023)
Aim: to analyze the perceptions of biological and social death reported by people living with HIV/AIDS after the diagnosis of this health condition. Methodology: The research in question has a qualitative and exploratory nature based on cartography, carried out in a reference center between July and October 2022, and used the user-guide tool, interview and field diary for data production. The interpretation occurred from the production of an analyzer. Results: the theme of dying is part of the daily lives of these people, for some individuals the diagnosis of HIV does not change their perspective of the future, but for others there is an important interdiction of life projects, generating an identity reconfiguration. Faced with these factors, facing the new reality produces powerful subjectivation processes. Thus, it is possible to see how sociability, mutual support and state support allow the rewriting of life. Final Considerations the fear of the diagnosis resulting from stigma, prejudice and discrimination is still present, and keeps them away from the care process. However, from a scenario of identity reorganization, they can produce power in life and in the construction of new existential modes.